Using Executable Specification and Regression Testing for Broadcast Mechanism of Visual Programming Language on Smartphones - Ali, Zulfiqar; Awwad, Aiman M Ayyal; Slany, Wolfgang (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The rapid advancement of mobile computing technology and the rising usage of mobile apps made our daily life more productive. The mobile app should operate all the time bug-free in order to improve user satisfaction and offers great business value to the end user. At the same time, smartphones are full of special features that make testing of apps more challenging. Actually, the quality is a must for successful applications and it cannot be achieved without testing and verification. In this paper, we present the Behavior Driven Development (BDD) methodology and Cucumber framework to automate regression testing of Android apps. Particularly, the proposed methods use the visual programming language for smartphones (Catrobat) as a reference. The Catrobat program scripts communicate via a broadcast mechanism. The objective is to test the broadcast mechanism from different angles and track regression errors as well as specify and diagnose bugs with the help of executable specifications. The results show that the methods are able to effectively reveal deficiencies in the broadcast mechanism, and ensure that the app matches all expectations and needs of end users.